2016
DOI: 10.1002/anie.201600656
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of a “Head‐to‐Middle” Prenyltransferase: Lavandulyl Diphosphate Synthase

Abstract: We report the first X-ray structure of the unique “head-to-middle” monoterpene synthase, lavandulyl diphosphate synthase (LPPS). LPPS catalyzes the condensation of two molecules of dimethylallyl diphosphate (DMAPP) to form lavandulyl diphosphate, a precursor to the fragrance lavandulol. The structure is similar to that of the bacterial cis-prenyl synthase, undecaprenyl diphosphate synthase (UPPS), and contains an allylic site (S1) in which DMAPP ionizes and a second site (S2) which houses the DMAPP nucleophile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…[5] Mcl22 from Streptomyces sp.C NH-189 similarly catalyzes the "head-to-middle" condensation of DMAPP and GPP to produce C 15 sesquilavandulyl diphosphate [eq. [8] Therefore,w ee xpected that as tructural comparison between CLDS and LPPS would provide crucial information about the unique reaction of CLDS,t hus advancing the knowledge of intricate terpene synthasecatalyzed reactions. [6,7] LPPS and Mcl22, however, are unable to catalyze the subsequent cyclization reaction as CLDS does.L PPS has been biochemically characterized, and its crystal structure has been reported recently.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[5] Mcl22 from Streptomyces sp.C NH-189 similarly catalyzes the "head-to-middle" condensation of DMAPP and GPP to produce C 15 sesquilavandulyl diphosphate [eq. [8] Therefore,w ee xpected that as tructural comparison between CLDS and LPPS would provide crucial information about the unique reaction of CLDS,t hus advancing the knowledge of intricate terpene synthasecatalyzed reactions. [6,7] LPPS and Mcl22, however, are unable to catalyze the subsequent cyclization reaction as CLDS does.L PPS has been biochemically characterized, and its crystal structure has been reported recently.…”
mentioning
confidence: 99%
“…TwoP Pi molecules in CLDS are located at the positions of the PPi molecules at the S1 and S2 sites in LPPS. [8] In CLDS,Arg60, which corresponds to Arg127 in LPPS,c ontacts (P1)O2 in as imilar manner to Arg127 in LPPS,s uggesting that Arg60 is involved in the release and stabilization of PPi. [8] TheT ris molecule lies at the position corresponding to the space between the hydrocarbon isoprene units of two DMAPP molecules in the LPPS structure ( Figure S3b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…X‐ray crystallography analyses have revealed that the protein structures of UPP synthase (UPPS), LPPS, CLDS, and Mcl22 adopt a typical fold for the cis ‐type IDS family (Figure ). These structures have allowed mechanistic and structural comparison among the cis ‐type IDS homologous enzymes.…”
Section: Coupling Mechanismmentioning
confidence: 99%
“…There are ∼70,000 such species known [2] , produced by a wide range of terpene synthases. Isoprenoids are of general interest since they are involved in the formation of important drugs [3] ; bacterial cell wall biosynthesis [4] ; fragrances [5] ; quinones and hemes for electron transport [6] as well as the post-translational modification of proteins that are important in cellular signaling [7] .…”
Section: Introductionmentioning
confidence: 99%